Diagnostik Klinis Malaria Di Kabupaten Musi Rawas Sumatera Selatan - Muhamad Nizar; Lukman Hakim (ASPIRATOR - Journal of Vector-borne Disease Studies, 2011)
now, AMI was reported to lower high while the MDG target of AMI up to 5 per 10,000 populationin 2015. This study aims to formulate the cardinal sign of clinical malaria in MusiRawas district. Two hundred and eleven samples were taken based on the inclusive case selectioncriteria include fever> 38°C, chills, sweating and headaches and muscle pain and anenlarged spleen in four health center with AMI > 10,000. There was no significant associationbetween the occurrence of clinical symptoms of malaria, but after the regression analysisobtained the cardinal sign of clinical diagnosis of malaria is fever> 38°C accompaniedthe headache, chills, cold sweat and nausea and age <39 years with OR 11.3. Clinical diagnosisis confirmed by the cardinal sign of fever > 38°C accompanied the headache, chills,sweating, muscle pain and age <39 years